An Efficent Distributed Medium Access Control for V2I VANET - Neelambike S; Chandrika J (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Provisioning smart intelligent transport for vehicular ad hoc networks (VANETs) depends on dissemination of safety-related messages. The performance of VANET are highly affected due vehicle density, mobility and environmental condition. Recently several research has been under development, the design of a rapid, flexible, efficient and reliable medium access control (MAC) which address the precise constraint of smart intelligent transport system in the highly dynamic VANET environment. Extensive survey carried out in this work shows TDMA (Time division medium access) based MAC approach outperform carrier sense medium access/ collision avoidance CSMA\CA based approach. However, TDMA based approach incurs bandwidth wastages. To utilize bandwidth more efficiently cognitive radio (CR) technique is adopted for designing efficient MAC. However, the existing CR model incurs computation overhead and is not evaluated under different environmental condition such as rural, highway and urban (RHU). To overcome research challenges, this work present efficient decentralized distributed MAC (DMAC) that minimize collision and maximize throughput. Experiment are conducted to evaluate the performance of DMAC over state-of-art model in terms of throughput, success transmission and collision achieved. The outcome shows significant performance over state-of-model.